CO2-Hydrophobin Structures Acting as Nanobombs in Beer: Part 1: A critical review of hypotheses and mechanisms - Deckers, Sylvie Marie; Gebruers, Kurt; Geert Baggerman, Geert Baggerman; Lorgouilloux, Yannick; Delcour, Jan A.; Michiels, Chris; Derdelinckx, Guy; Martens, Johan; Neven, Hedwig (BrewingScience, 2010)
Primary beer gushing is defined as the wild and uncontrolled overfoaming of packaged beer induced by contaminated raw materials as barley and malt. It is generally admitted that most probably amphipathic molecules such as hydrophobins and non-specific lipid transfer proteins (ns-LTPs) are responsible for this phenomenon. These molecules are synthesized by moulds and by vegetal tissues respectively in order to modify the polarity of surfaces and the solubility of molecules. At present, hydrophobins are extensively studied as they are considered as the major responsible molecules involved in primary gushing. Although a strong reduction (more than 85 %) of the initial concentration of hydrophobins present in malt occurs during the brewing process, the residualquantity remaining in finished beer is sufficient to provoke the gushing of packaged beer and the subsequent dramatic commercial damages to a particular beer brand. This review compiles the relevant fundamental physical and chemical properties of CO2 and experimental observations at laboratory and pilot scale. A plausible mechanism of primary gushing is presented. It is based on the effective role of hydrophobins association to CO2 nanobubbles, acting as “nanobombs” and perhaps as “nucleation sites” causing effects from overfoaming to strong gushing depending on the concentration and the carbonation rate. In beer formation of CO2 bubbles proceeds through heterogeneous nucleation. The rapid heterogeneous nucleation initiated at the opening of the container in excessively gushing beer suggests the the presence of catalysts to overcome the energy barriers. Since hydrophobin molecules are able to bind to carbonic acid, they prevent part of the CO2 from dissolution. These structures will aggregate in timeframes of days or even weeks depending on the beer by forming nanobubbles of a typical critical radius. The internal pressure of these nanobubbles is proportional to the carbonation pressure of gaseous CO2 in the container at filling (about 3.0 till 4.0 ATU of CO2 ). At the opening of the container, the difference of partial pressure of carbonic acid in the bottle and in the atmosphere provokes the explosion of these nanobubbles and results in a strong gushing effect.